Nanoparticle delivery of CRISPR into the brain rescues a mouse model of fragile X syndrome from exaggerated repetitive behaviours. (July 2018) - Lee, Bumwhee; Lee, Kunwoo; Panda, Shree; Gonzales-Rojas, Rodrigo; Chong, Anthony; Bugay, Vladislav; Park, Hyo; Brenner, Robert; Murthy, Niren; Lee, Hye
Abstract Technologies that can safely edit genes in the brains of adult animals may revolutionize the treatment of neurological diseases and the understanding of brain function. Here, we demonstrate that intracranial injection of CRISPR–Gold, a nonviral delivery vehicle for the CRISPR–Cas9 ribonucleoprotein, can edit genes in the brains of adult mice in multiple mouse models. CRISPR–Gold can deliver both Cas9 and Cpf1 ribonucleoproteins, and can edit all of the major cell types in the brain, including neurons, astrocytes and microglia, with undetectable levels of toxicity at the doses used. We also show that CRISPR–Gold designed to target the metabotropic glutamate receptor 5 (mGluR5) gene can efficiently reduce local mGluR5 levels in the striatum after an intracranial injection. The effect can also rescue mice from the exaggerated repetitive behaviours caused by fragile X syndrome, a common single-gene form of autism spectrum disorders. CRISPR–Gold may significantly accelerate the development of brain-targeted therapeutics and enable the rapid development of focal brain-knockout animal models. Gene editing of a single gene in the brain of an adult mouse model of fragile X syndrome, achieved via the intracranial injection of a nonviral Cas9 delivery vehicle, rescues mice from the exaggerated repetitive behaviours caused by the disease.